Composite light ropes model-based dynamics force prediction model of high speed dry milling UD-CF/PEEK considering size effect. (April 2022) - Song, Yang; Qu, Da; Wu, Bo; Cao, Huajun
Abstract: As an emerging material, Carbon fiber reinforced polyetheretherketone (CF/PEEK) is widely used in aviation, automotive, sports products, medical equipment and other high-end manufacturing industries due to its high shock resistance, thermostability, and recyclability. However, its dry-machining is an unclear dynamic material removal process which limits the machining efficiency and surface quality. To this end, we first presented composite light ropes model in machining composites considering size effect. Based on composite light ropes model, cutting region is affected by bending, stretching, pressing, bouncing and delamination, as the cutting mechanisms of carbon fiber and matrix are different. The carbon fibers distribution in chip is first introduced into the model to confirm the fiber deformation at different position. Based on composite light ropes model and elastic-plastic theory, the cutting force prediction model is obtained. To complete the model, the free-damped vibration force prediction model is established in empty cutting stage. The dynamics force prediction model is proofed with high prediction accuracy. Besides, the influences of cutting parameters on cutting and vibration force are analyzed by nonlinear regression analysis. It demonstrated that size effect is of great importance in establishing cutting force prediction model and revealing cutting mechanisms of CF/PEEK. Graphical abstract: Unlabelled Image Highlights: Composite light ropes model is first used in dynamics force prediction model of milling CFRP. The interface in CFRP is studied in dynamics force prediction model. Carbon fibers distribution model in chip is introduced into the model.